Science, creation and the Bible : reconciling rival theories of origins - Carlson, Richard F., 1936-; Longman, Tremper (Downers Grove, Ill. : IVP Academic, 2010)
Physicist Richard Carlson and biblical scholar Tremper Longman address the longstanding problem of how to relate scientific description of the beginnings of the universe with the biblical creation passages found in Genesis chapters 1 and 2. Experts in their respective fields, these two authors provide a way to resolve the seeming conflicting descriptions by showing the meaning of the biblical texts as well as the meaning of scientific description.--From publisher description.
Theological and scientific sources and their interpretation -- Characteristics of theology and science relevant to the conflict -- Biblical interpretation : a key element in resolving the creation-evolution conflict -- Creation in the Old Testament -- Creation in the New Testament -- Genesis 1:1-2:3 and Genesis 2:4-25 -- Genesis 1 and 2 as a worldview statement of the ancient people of Israel.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Creationism; Creation; Religion and science; Bible. -- Criticism, interpretation, etc; RELIGION / Christian Theology / General; Electronic books